Data for: Soil properties, microbial respiration, and microbial growth, for determining resource limitation for microbial growth in climate change simulation treatments in the Subarctic - Yuan, Mingyue; Hicks, Lettice; Rousk, Johannes (Lund University, 2023)
The data was from a study about resource limitation for soil microbial growth in climate change simulation treatments in the subarctic. The data include soil properties, microbial respiration, and microbial growth. Soil properties including soil water content, soil organic matter, and electrical conductivity, were measured to detect if our field treatments (i.e., nitrogen fertilisation and plant litter addition in a tundra ecosystem in Abisko, Sweden) had any effect on soil physicochemistry. Microbial biomass was estimated by phospholipid-derived fatty acids, to detect the effects of field treatments on soil microbial biomass. Soil microbial growth rates were measured by Bacterial growth was estimated by 3H-leucine incorporation into proteins and 3H thymidine incorporation into DNA. Fungal growth was estimated using the 14C-acetate incorporation into ergosterol method. Soil respiration rate (as CO2 produced by microbes during a certain time) was determined using a gas chromatograph. For more details about the experiment design and the calculation, please see the file “Field and laboratory”.

Dessa data avser studien "Soil properties, microbial respiration, and microbial growth, for determining resource limitation for microbial growth in climate change simulation treatments in the Subarctic". Se beskrivningen på engelska för närmare information.
Data för: Soil properties, microbial respiration, and microbial growth, for determining resource limitation for microbial growth in climate change simulation treatments in the Subarctic
Keywords: microbial ecology; mikrobekologi; Natural Sciences; Naturvetenskap; Environmental Sciences; Miljövetenskap; Microbiology; Mikrobiologi; Ecology; Ekologi